Covid-19 Pandemic: Educational Transformation at Paramount Elementary School Palembang - Happy Fitria; Ali Maksum; Muhammad Kristiawan (AL-ISHLAH: Jurnal Pendidikan, 2021)
With the increasing limited face-to-face learning methods due to the Covid-19 pandemic, there is a transformation process carried out in the education system. One of them is changing the new landscape of the education system at the primary, secondary, and higher education levels. The digital transformation of teachers and students is the impact of the learning process during the Covid-19 pandemic. This study is qualitative research that aims to determine how learning during the Covid-19 pandemic for one year at Paramount Palembang school was. The study results illustrate that the impact of the pandemic has caused adverse effects in the world of education due to the shift from conventional methods to online methods. However, the impact of this change is not always negative. Without realizing it, education has undergone a monumental transformation that forces all parties to change and be aware of the importance of technology in life, especially in education. The journey of transformation in each region as a result of the Covid-19 pandemic is undoubtedly different. The study results show that the journey of education transformation during the one-year Covid-19 pandemic at Paramount Palembang schools shows that all teachers enjoy this change and feel the benefits. The results of this study are significant to become the basis for the transformation of the education system in schools and education in general. The following policy is how all students can enjoy education transformation by integrating learning methods into online and offline learning.